Evaluation of Masticatory Performance and Patient Satisfaction Before and After Posterior Implant Restoration - Zulkarnaen, Filzah (2021)
Objective: To evaluate the improvement in masticatory performances two weeks after posterior implant restoration. Material and Methods: Nine patients with missing first and second molars were included in the study. Masticatory performances were evaluated using subjective and objective methods utilizing color-changeable chewing gum and the visual analog scale (VAS) assessment. The subjects were asked to chew the color-changeable chewing gums before and two weeks after the posterior implant restoration. Their expectations regarding aesthetics and function were verified on the VAS before implant placement. Additionally, the VAS was used for the posttreatment completion rating two weeks after the implant restoration. Results: Significant differences in masticatory performance were noted at baseline (before implant posterior restoration) and two weeks after implant restoration (p<0.05). The posttreatment aesthetic and functional expectations ratings significantly exceeded the expectations (p<0.05). Conclusion: Masticatory performances were improved two weeks after implant restoration. In addition, the significant posttreatment ratings of the patients exceeded their initial expectations. In particular, patients with poor masticatory functions demonstrated significant improvements and satisfaction following implant restoration compared to those with good mastication. These findings indicate that a posterior implant restoration can increase the masticatory performance.